Pendidikan Karakter Anak Dalam Keluarga (Studi Kasus: Peran Ayah Sebagai Orang Tua Tunggal di Nagari Pasir Talang Kecamatan Sungai Pagu Kabupaten Solok Selatan) - Mhoren Puspita Sari; Nora Susilawati (Universitas Negeri Padang, 2022)
This study aims to explain the role of fathers as single parents in implementing children's character education in Nagari Pasir Talang, Sungai Pagu District, South Solok Regency. This research uses a qualitative approach with a case study type of research type intrinsic case studies. The results of the study reveal the role of fathers in inculcating character values, namely (1) Fathers educate their children with religious values, which are carried out by fathers by inculcating religious values starting from praying, covering their genitals, and doing good, (2) Fathers guiding children through discipline, namely the application of moral values. character values of self-discipline, discipline of neatness, and discipline of time, (3) Fathers as friends for their children, namely the application of communicative character values through the community and in the family environment, (4) Fathers as mentors for their children, namely the application of independent character values, starting from independently at home and at school.